Mensurações do bulbo ocular e cálculo do poder dióptrico da lente intraocular em miniporcos - Barros, R. [UNESP]; Rodrigues, A. C.L. [UNESP]; Guberman, U. C. [UNESP]; Gandolfi, M. G. [UNESP]; Merlini, N. B. [UNESP]; Teixeira, C. R. [UNESP]; Padovani, C. R. [UNESP]; Brancalion, B. B. [UNESP]; Ranzani, J. J.T. [UNESP]; Brandão, C. V.S. [UNESP] (FapUNIFESP (SciELO), 2016)
The aim of this study was to determine the refractive power of intraocular lens (IOL) of mini pigs and the dimensions of the eyeball. A total of 17 (34 eyes) healthy, adult, males and female animals, with average weight of 70kg were used. For every eye, A-mode ultrasound, keratometry and the measurement of limboto- limbo distance were conducted, all variables for calculating the refractive power of the IOL. The value was obtained using different formulas and Holladay IOL Consultant® Software. Additionally, the ocular measurements were compared per sex, laterality of the eye and the different formulas used in this study (Haigis, Hoffer Q, SRK / T, Holladay I and Holladay II). In the comparison between sex and laterality of the eye, there was no difference in biometric variables and power of the IOL. The application of the employed formulas (Haigis, Holladay II, Holladay I, SRK / T and Hoffer Q) allowed the IOL power calculation for this specie, and the observed value ranged between 39.58±2.15 and 46.60±2.81 diopters. Mini pigs play an important and growing role as an experimental model for study and practice of ophthalmic procedures, specially related to their smaller size and easy management in long-term experiments.
Ocular bulb measurements and diopter power calculation of the lens in minipigs
Keywords: Biometry; Cataract; IOL; Keratometry; Mini pig